Weight Bias Internalization Among Adolescents Seeking Weight Loss: Implications for Eating Behaviors and Parental Communication - Puhl, Rebecca M.; Himmelstein, Mary S. (Frontiers in Psychology, 2018)
Background: Emerging evidence has demonstrated a high prevalence of weight bias internalization (WBI) among adults, as well as consistent links between internalization and adverse psychological and physical health. However, research examining WBI in youth and its impact on their health is scarce, especially among youth seeking weight loss treatment who may be particularly vulnerable to weight stigma from peers and parents. To address this research gap, the present study assessed WBI in a weight loss treatment-seeking sample of adolescents, examining associations between internalization and adolescents’ eating behaviors and parental weight-related communication. Methods: Adolescents (N = 148, Mage = 15.97 years), completed online self-report measures to assess WBI (using the modified version of the WBI Scale), body weight, binge eating, eating as a coping strategy, and weight teasing from peers and family members. Adolescents also reported on the frequency of parental comments about body weight, parental dieting, and parental encouragement of adolescent dieting. Results: Adolescents expressed a high mean level of internalized weight bias (M = 5.45, SD = 0.88). Higher levels of internalization were observed across increasing body weight categories; no differences were observed for gender or history of weight teasing. WBI was significantly higher among adolescents who reported binge eating and eating to cope with distress. Regression analyses showed that weight-related comments from mothers (but not fathers) significantly predicted adolescents’ WBI (including frequency of mothers’ comments about adolescents’ body weight, comments about their own body weight, and encouragement of their adolescent to diet), as did increased dieting frequency among mothers. Conclusion: The present study provides novel insights to the scant literature on WBI in youth. Findings indicate that WBI is high in both girls and boys engaged in weight loss, and is associated with maladaptive eating behaviors, higher frequency of maternal dieting, and mothers’ comments about body weight. These findings have important clinical implications for youth and families engaged in weight loss treatment, and underscore the need for research to clarify adverse effects of internalization on weight-related health in youth and to better understand the role that parental weight communication may have on adolescents’ internalization.